Autoimmunizacyjne zespoły gruczołowe u dzieci - przebieg kliniczny i klasyfikacja na podstawie analizy wybranych przypadków - Fagasińska, Paulina; Piotrkowicz, Magdalena; Wnuk, Agnieszka; Czyżewska, Ewa; Artemniak-Wojtowicz, Dorota; Kucharska, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Autoimmune polyglandular syndrome, APS, is characterised by the presence of two or more chronic autoimmune organ-specific diseases in one individual. There are four types of APS; however, variable clinical course often makes the proper APS-type diagnosis difficult. In this paper, we would like to present 3 patients with APS, whose diagnosis has changed over time. The first patient was a girl with alopecia and normocytic anaemia, both of which occurred when she was 9 years old. At the age of 12, an autoimmune thyroiditis was diagnosed, and antibodies against adrenal cortex were found when she turned 17. The second patient was a 10-year-old boy admitted to the hospital because of vomiting, stomach ache and stomatitis/candidiasis. He also suffered from polydypsia and decreased appetite for several days. Type 1 diabetes and Addison's disease had been diagnosed. The third patient was a 16-year-old female with acute thrombocytopenia and anaemia accompanied by Graves' disease. Additionally, during the course of the disease, she developed symptoms of lupus-like syndrome and central facial nerve palsy. The described cases indicate that the course of the disease as well as the diagnosis of the patient with APS may change over time. Atypical development of an autoimmune disease or atypical response for standard treatment should lead to extensive diagnosis towards new elements of the syndrome. Every organ-specific autoimmune disease might be the first prodrome of APS.